2007
DOI: 10.1007/s00439-007-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

High-density single nucleotide polymorphism array analysis in patients with germline deletions of 22q11.2 and malignant rhabdoid tumor

Abstract: Malignant rhabdoid tumors are highly aggressive neoplasms found primarily in infants and young children. The majority of rhabdoid tumors arise as a result of homozygous inactivating deletions or mutations of the INI1 gene located in chromosome band 22q11.2. Germline mutations of INI1 predispose to the development of rhabdoid tumors of the brain, kidney and extra-renal tissues, consistent with its function as a tumor suppressor gene. We now describe five patients with germline deletions in chromosome band 22q11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 43 publications
4
64
0
2
Order By: Relevance
“…MLPA-HD confirmed the findings of FISH with probes from the rhabdoid tumor region and microarray analysis [Jackson et al, 2007]. Figure 2, Patients 17-24, represent the findings on these patients.…”
Section: Constitutional 22q112 Deletions Associated With Rhabdoid Tumorsupporting
confidence: 58%
“…MLPA-HD confirmed the findings of FISH with probes from the rhabdoid tumor region and microarray analysis [Jackson et al, 2007]. Figure 2, Patients 17-24, represent the findings on these patients.…”
Section: Constitutional 22q112 Deletions Associated With Rhabdoid Tumorsupporting
confidence: 58%
“…In contrast, frameshift and nonsense mutations are mostly associated with RTs, with early development. Finally, germline 22q11.2 deletion, so far only observed in RTs, may be linked to a later onset of tumor (17,(29)(30)(31). In this respect, patients 24 and 25, both with germline 22q11.2 deletions, harbored the latest RTs ever reported in a context of hSNF5/INI1 constitutional mutations (8 and 22 years, respectively).…”
Section: Discussionmentioning
confidence: 86%
“…In this respect, patients 24 and 25, both with germline 22q11.2 deletions, harbored the latest RTs ever reported in a context of hSNF5/INI1 constitutional mutations (8 and 22 years, respectively). Miscellaneous polymalformative conditions, such as velocardiofacial and Goldenhar syndromes, have been reported in patients with large 22q11.2 deletions (17,30), but bladder exstrophy, occasionally related to 22q11.2 duplication (32, 33), has not been reported in these cases. Hence, the association between RPS and bladder exstrophy in our case remains unexplained.…”
Section: Discussionmentioning
confidence: 95%
“…10 Distal 22q11.2 microdeletions that span the LCR22-F to -G interval encompassing the tumor suppressor SMARCB1 gene (also called INI1) have been reported to manifest many of the presenting features mentioned above but also have high incidence of malignant rhabdoid tumors in infancy and early childhood, predominantly in the kidneys and central nervous system, which necessitates tumor surveillance in these patients. [19][20][21][22][23][24] Depending on the mediating LCR22s, the distal 22q11.2 microdeletions can vary in size between ~700 kb and ~3.0 Mb. To date, the distal 22q11.2 microdeletions have been grouped together as a single clinical entity despite the fact that these deletions comprise several partially overlapping and nonoverlapping deletions of varying size.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, deletions in the distal 22q11.2 region that span the LCR22-F to -G interval including the SMARCB1 gene have been reported in multiple studies and were shown to be also variable in size and share many of the presenting features of the distal 22q11.2 microdeletion phenotype discussed earlier, in addition to a very high incidence of malignant rhabdoid tumors in infancy and early childhood. [19][20][21][22][23][24] Accordingly, we propose categorizing the distal 22q11.2 microdeletions into three genomic types: type I: with deletions flanked by LCR22-D and either -E or -F; type II: with deletions flanked by LCR22-E and -F; and type III: with any deletion in this region minimally spanning the LCR22-F to -G interval and encompassing the SMARCB1 gene (Figure 2). All three deletion types are thought to be pathogenic and are most often de novo.…”
Section: Discussionmentioning
confidence: 99%